HASBI ASH-SHIDDIEQY'S THOUGHTS IN THE PEARL OF HADITH: INTERTEXTUAL ANALYSIS OF IDEA - Ahmad Fibrianto; Jannatul Husna; Waharjani Waharjani (Universitas Muhammadiyah Surakarta, 2023)
It is hoped that this research can decide how to examine the intertextual ideas of Hasbi Ash-Shiddieqy's thoughts in one of his works, the pearl of hadith. From researching his work entitled